Effect of Nutrition Education through Pegia e-Health on Mothers’ Knowledge, Attitudes, Practices and Their Impact on Nutritional Intake of Children Aged 3-6 years - Purnamasari, Dyah Umiyarni; Agustia, Friska Citra (Poltekkes Kemenkes Yogyakarta, 2025)
Background: Mothers’ nutritional knowledge, attitudes, and practices influence children's feeding habits. Therefore, mothers are expected to receive appropriate nutrition education to improve dietary behaviors. This research aimed to analyze the influence of nutrition education through Pegia e-Health on mothers’ nutritional knowledge, attitudes, and practices, as well as its impact on the nutritional intake of children aged 3-6 years. Method: The design used a quasi-experimental pretest-posttest group. This research was conducted for 12 weeks, and the total number of respondents was 54 mothers with children aged 3-6 years from 8 preschool institutions in Banyumas Regency. Results: There was a significant increase in median knowledge, attitudes, and nutrition practice scores by 8.0, 5, and 1.0 points (p: 0.000 <0.05). Furthermore, there was a significant increase in nutritional intake, including 31.15 g of carbohydrates, 1.44 g of fiber, and 380.07 RE (Retinol Equivalents) of vitamin A (p <0.05). Conclusion: Pegia e-Health had an impact on improving mothers’ knowledge, attitudes, and practices, as well as the increase in carbohydrate, fiber, and vitamin A intake in children. It was recommended that mothers increase the frequency and access time to Pegia e-Health to improve their dietary behaviors.